Falešná argumentace a verbální agrese v politické komunikaci - Svobodová, Jindřiška (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2017)
ture of communication in interpersonal exchanges and in mass media as well as in political discourse. The aggression in the socio-psychological sense is based in instinctive self-defense (or defense of one´s own territory); seen in the broader framework of social interaction, aggressive communication occurs in two forms: a/ as a hostile aggression which is impulsive, driven by anger and primarily aiming at harming the target; b/ as an instrumental aggression which is premeditated as a means of retaliation or obtaining some goal. Analyses of dialogues should demonstrate that the aggressive/openly offensive communication can be seen not just as a borderline case of impoliteness but, more accurately, as a parallel phenomenon, a communicative strategy which can use vulgarities but can dispense with them as well. An offensive and inconsiderate communicative strategy does not necessarily imply openly vulgar communication or the usage of derogatory language. On the other hand, using argumentative fallacies, i.e. arguments ad hominem rather than ad rem, may belong to the examples of inconsiderate and offensive communication strategies. Předkládaný text je věnován problematice verbální agrese, a to zejména v mediál- ním politickém diskurzu. Agrese má v původním sociálně-psychologickém smyslu původ v instinktivní sebeobraně a v obraně vlastního teritoria, v širším rámci spole- čenské interakce se pak projevuje ve dvou formách, a to jednak jako impulzivní reakce na starší či aktuální podnět, jednak jako komunikační nástroj záměrně užitý při dlouhodobém dosahování vlastních cílů. V předkládané analýze chceme dokázat, že verbální agresi nelze ztotožňovat s pragmalingvisticky chápanou kategorií nezdvořilosti. Jde o primárně útočnou komunikaci, která nemusí být nutně spojována s užitím hrubých či vulgárních výrazů, ale v níž se (a to zejména v prostředí politické komunikace) objevuje útok na tvář oponenta spojený např. s užitím falešných argumentačních strategií.
Keywords: aggressivity; argumentation; verbal aggression; im/politeness; rudeness; offense; personal identity attack; self presentation; dehonestation